Pengembangan Model Pembelajaran Permainan Colorful Balls Run Untuk Reaksi Gerak Pada Anak Tunagarhita (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to determine the products of The Development of Learning Colorful Balls Run for Motion Reaction of mentally disabled children of SLB Negeri Semarang grade V in the academic year of 2015.. This research is the development (research and development / R & D), which consists of 10 steps of research, namely the potential and problems, data collection, product design, design validation, design revisions, test products, product revision, trial use, testing products, mass production Because the average obtained from the experts of physical education teacher 80% (good) and from learning experts gained 92% (very good). The results of trial I product of small group on cognitive aspects was 83.53% (good), affective aspects was 82.10% (good), psychomotor aspects was 81.39% (good), the average of trial I was 82.34% (good). The results of trial II, the large group in the cognitive aspects was 85.14% (good) affective aspects was 83.76% (good) psychomotor aspects was 83.07% (good), the average of trial II was 83.99% (good). It was concluded that the development of colorful balls run game model can be used as an alternative to learn sport especially small ball game for V graders of SLB Negeri Semarang.